At the margins of biomedicine: the ambiguous position of 'Registered Medical Practitioners' in rural Indian healthcare. Issue 4 (2nd December 2016) - Nahar, Papreen; Kannuri, Nanda Kishore; Mikkilineni, Sitamma; Murthy, G.V.S.; Phillimore, Peter
Abstract: This analysis challenges a tendency in public health and the social sciences to associate India's medical pluralism with a distinction between biomedicine, as a homogeneous entity, and its non‐biomedical 'others'. We argue that this overdrawn dichotomy obscures the important part played by 'informal' biomedical practice, an issue with salience well beyond India. Based on a qualitative study in rural Andhra Pradesh, South India, we focus on a figure little discussed in the academic literature – the Registered Medical Practitioner (RMP) – who occupies a niche in the medical market‐place as an informal exponent of biomedical treatment. We explore the significance of these practitioners by tracking diagnosis and treatment of one increasingly prominent medical 'condition', namely diabetes. The RMP, who despite the title is rarely registered, sheds light on the supposed formal‐informal sector divide in India's healthcare system, and its permeability in practice. We develop our analysis by contrasting two distinctive conceptualisations of 'informality' in relation to the state in India – one Sarah Pinto's, the other Ananya Roy's.